2014
DOI: 10.1017/s0025315414000277
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of pigmentation features among North Atlantic killer whale (Orcinus orca) populations

Abstract: Here we present a comparison of saddle and eye patch patterns of killer whales from Norwegian, Icelandic, British, Spanish and Greenlandic waters. We found only a small amount of variation in saddle patch shapes, which may reflect a recent phylogenetic divergence from the most recent common ancestor. Eye patch shapes were more variable than saddle patches in small details. Most individuals had eye patches with parallel orientation, with the exception of a small group of killer whales from the Hebrides, which, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…), and Mäkeläinen et al . () found no effect of sex on eye patch size. The same analyses were performed to test for sex differences in dorsal fins, saddle patches, and eye patches, and determine whether it was appropriate to analyze them separately.…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…), and Mäkeläinen et al . () found no effect of sex on eye patch size. The same analyses were performed to test for sex differences in dorsal fins, saddle patches, and eye patches, and determine whether it was appropriate to analyze them separately.…”
Section: Methodsmentioning
confidence: 88%
“…Globally, quantitative studies of the morphological differences among killer whale ecotypes have been limited (Baird and Stacey , Visser and Mäkeläinen , Mäkeläinen et al . ). These studies have utilized the frequency of occurrence of broad pigmentation patterns to examine differences between killer whale populations.…”
mentioning
confidence: 97%
“…On the other hand, although cetaceans are highly migratory species, they often show subpopulations with high fidelity to small areas. Thus, for example, a population of killer whales Orcinus orca from Hebrides Islands showed a different pigmentation pattern when compared with neighboring populations [58]. Cheney et al [59] also suggested the existence of three parapatric communities of bottlenose dolphins (Tursiops truncatus) in Scottish coastal waters, two of them located in the west coast.…”
Section: Genetic Diversity and Population Structure Of A Simplex Infe...mentioning
confidence: 99%
“…Photo‐identification analysis was conducted via the commonly accepted standard (Bigg, 1982), and further included eye‐patch comparisons (Mäkeläinen et al, 2014), depending on availability and quality of images. Identification photographs from Spain, Italy, and Lebanon were compared via visual analysis to the already existing data set of 322 North Atlantic killer whales cataloged in West Iceland (M.‐T.M., unpublished data).…”
Section: A/n Date Time Sn113 Sn114 Sn115 Sn116 Calf#1 Calf#2 Ind Tota...mentioning
confidence: 99%